Γ valley transition metal dichalcogenide moiré bands - Angeli, Mattia (Proc Natl Acad Sci U S A, 2021)
The valence band maxima of most group VI transition metal dichalcogenide thin films remain at the [Formula: see text] point all of the way from bulk to bilayer. In this paper, we develop a continuum theory of the moiré minibands that are formed in the valence bands of [Formula: see text]-valley homobilayers by a small relative twist. Our effective theory is benchmarked against large-scale ab initio electronic structure calculations that account for lattice relaxation. As a consequence of an emergent [Formula: see text] symmetry, we find that low-energy [Formula: see text]-valley moiré holes differ qualitatively from their [Formula: see text]-valley counterparts addressed previously; in energetic order, the first three bands realize 1) a single-orbital model on a honeycomb lattice, 2) a two-orbital model on a honeycomb lattice, and 3) a single-orbital model on a kagome lattice.